The Shape Shifter - Book 18 - Hillerman, Tony (New York : HarperCollins, 2006)
"Retired from the Navajo Tribal Police, Lieutenant Joe Leaphorn is called upon once again to solve a crime. This time it's Joe's last case, a case that remains unsolved and contines to haunt him."--From source other than the Library of Congress
Accelerated Reader AR
Keywords: Leaphorn, Joe, Lt. (Fictitious character) -- Fiction; Chee, Jim (Fictitious character) -- Fiction; Indian reservation police -- Fiction; Police -- Fiction -- New Mexico; Navajo Indians -- Fiction; New Mexico -- Fiction; Fiction